Characterization of Jelly Candy from Seaweed (Gelidium sp.) and Gelatin - Manurung, Estherella; Putri, Raja Marwita Sari; Suhandana, Made (Marinade, 2018)
Jelly candy was formulated with additional Gelidium and gelatin. Gelidium and gelatin contain components that can improve the texture. The objective of this study was to know the chemical quality from Gelidium sp. jelly formulation. Three treatments GA (content of Gelidium was 63,2%), GB (content of Gelidium was 61,80%) and GC (content of Gelidium was 60,4%) were analyzed to see their chemical quality. The highest moisture content was obtained at GA treatment (19,13%). The highest ash content was obtained at GC treatment (0,45%). The highest sugar content obtained at GB treatment (55,22%). The highest Protein content obtained at GC treatment (21,89%). The lead (Pb) unidentified in a product after formulation.